The extended mind the power of thinking outside the brain - Paul, Annie Murphy (Boston Houghton Mifflin Harcourt, 2021)
The Extended Mind outlines the research behind this exciting new vision of human ability, exploring the findings of neuroscientists, cognitive scientists, psychologists, and examining the practices of educators, managers, and leaders who are already reaping the benefits of thinking outside the brain. She excavates the untold history of how artists, scientists, and authors?from Jackson Pollock to Jonas Salk to Robert Caro?have used mental extensions to solve problems, make discoveries, and create new works. In the tradition of Howard Gardner?s Frames of Mind or Daniel Goleman?s Emotional Intelligence, The Extended Mind offers a dramatic new view of how our minds work, full of practical advice on how we can all think better.
Includes bibliographical references and index.
Keywords: Mind and body